2014
DOI: 10.5534/wjmh.2014.32.2.76
|View full text |Cite
|
Sign up to set email alerts
|

A Milk Protein, Casein, as a Proliferation Promoting Factor in Prostate Cancer Cells

Abstract: PurposeDespite most epidemiologic studies reporting that an increase in milk intake affects the growth of prostate cancer, the results of experimental studies are not consistent. In this study, we investigated the proliferation of prostate cancer cells treated with casein, the main protein in milk.Materials and MethodsProstate cancer cells (LNCaP and PC3), lung cancer cells (A459), stomach cancer cells (SNU484), breast cancer cells (MCF7), immortalized human embryonic kidney cells (HEK293), and immortalized no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 27 publications
0
10
0
5
Order By: Relevance
“…At best, a recent in vitro study reporting that caseins (typical milk proteins) could promote proliferation of PC3 and LNCaP prostate cancer cells argues against our results. However, these effects i) were obtained at extremely high casein concentration (1 mg/mL), ii) were not validated in vivo [ 38 ], and iii) only involved a single milk protein family out of the complex nature of ingredients constituting milk. Taken together, it is fair to claim that, globally, milk does not promote prostate tumor progression in Pb-Prl and KIMAP mice.…”
Section: Discussionmentioning
confidence: 99%
“…At best, a recent in vitro study reporting that caseins (typical milk proteins) could promote proliferation of PC3 and LNCaP prostate cancer cells argues against our results. However, these effects i) were obtained at extremely high casein concentration (1 mg/mL), ii) were not validated in vivo [ 38 ], and iii) only involved a single milk protein family out of the complex nature of ingredients constituting milk. Taken together, it is fair to claim that, globally, milk does not promote prostate tumor progression in Pb-Prl and KIMAP mice.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some studies drew opposite conclusions. Park et al confirmed that the milk protein casein promoted the proliferation of prostate cancer cells through in vitro assay [ 6 ]. Kroenke et al harbored the view that high-fat dairy intake was associated with poor prognosis after breast cancer diagnosis, however no significant effect was found with respect to low-fat dairy intake [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, most of the reviews point to a positive association between milk consumption and the incidence or increase of PC risk. However, there is strong evidence in the literature (not reviews) that associates dairy consumption and PC (91) and disease progression (82, 133), and possibly initialization (82). Through this review of the literature we understand the different mechanisms triggered by nutrients contained in milk and derivatives that may lead to an increased risk of prostate cancer in its consumers.…”
Section: Discussionmentioning
confidence: 99%